Analysis of the Effectiveness of Online-Based Patient Queue Management System Innovation: A Study at UMY Dental Hospital - Kusumastiwi, Rr. Pipiet Okti; Regia Aristyanto; Fahmi Yunisa (Community Medicine and Education Journal, 2024)
Long queues and long waiting times at dental and oral health services are frequent complaints from patients. This is caused by the time for dental and oral procedures which generally takes quite a long time compared to other health services. UMY Dental Hospital implemented innovation in the form of an online patient queue management system to overcome this problem. This research aims to evaluate the effectiveness of the online queuing system. This study used a non-experimental observational design with a cross-sectional approach. Data was collected through a survey of 1000 patients who used the UMY Dental Hospital online queue system. Data were analyzed using descriptive statistics and inferential statistical tests. The research results show that the UMY Dental Hospital online queuing system is effective in reducing patient waiting time. The average patient waiting time with the online queuing system was 21.33 (SD 1.45) minutes, shorter than with the manual queuing system which averaged 112.32 (SD 8.23) minutes. Patients were also satisfied with the online queuing system, with 92.32 (SD 4.21) respondents stating they were satisfied. The online patient queue management system at UMY Dental Hospital has proven effective in reducing patient waiting time and increasing patient satisfaction. This system can be a model for other dental hospitals to improve the quality of their services.